Time Flies When You're Having Fun: AMJ, 2005–2007 - Rynes, Sara L. (Academy of Management Journal, 2007)
The author offers opinions on her tenure as editor of the publication from 2005-2007. The editorial board's goals of making the publication of more professional interest, of increasing the transparency of its review process, and of making it more internationally focused are given, and the steps taken to meet them are described. The author thanks her colleagues and readers, and states that her successor will do an excellent job.